Ketersediaan dan Kebutuhan Air Daerah Irigasi Ameroro Kabupaten Konawe - Haydir Haydir; Abdul Aman Ega; Iksan Saputra; Ahmad Syarif Sukri; Hasddin Hasddin (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
In general, sources of agricultural irrigation in Indonesia still rely on rainwater, so the productivity of wetland agriculture, especially rice, is highly dependent on rainwater as an agricultural input. In this position, irrigation (weirs) is important in maintaining the availability of water for agricultural irrigation needs. This study aims to analyze water availability and water demand from Ameroro Irrigation. Both of these results provide information (pattern) of farmer planting. Research data comes from primary and secondary. Comparative analysis of the supply and demand for irrigation water using the Penman method and the F.J. Mock method to determine the amount of water flow from rainfall data, the hydrological characteristics of the catchment area, and evapotranspiration. The results of this study position that the construction of the Ameroro Dam has a vital role in maintaining the balance of irrigation (inflow and outflow). Maintaining this balance is at the same time the basis for irrigation engineering management efforts for agricultural activities. For farmers, those who live on or cultivate functional agricultural land A, B, and C start the planting season in May or in another month taking into account that the maximum plant growth period does not occur in the October period.